Role of colonoscopic biopsy in distinguishing between Crohn's disease and intestinal tuberculosis. Issue 8 (27th July 2006) - Kirsch, R; Pentecost, M; de M Hall, P; Epstein, D P; Watermeyer, G; Friederich, P W
Abstract : Background: The histological differential diagnosis of Crohn's disease and intestinal tuberculosis can be very challenging, as both are chronic granulomatous disorders with overlapping histological features. Aim: To evaluate selected clinical and histological parameters in colonic biopsy specimens for their ability to discriminate between Crohn's disease and intestinal tuberculosis. Methods: 25 patients with Crohn's disease and 18 patients with intestinal tuberculosis were selected for this study on the basis of established clinical, radiological and histological criteria. Clinical data and selected histological parameters in colonoscopic biopsy specimens were assessed retrospectively. A total of 103 and 41 biopsy sites were evaluated in patients with Crohn's disease and intestinal tuberculosis, respectively. Results: Clinical parameters helpful in differentiating intestinal tuberculosis from Crohn's disease included chest radiographic features of tuberculosis (56% v 0%), perianal fistulae (0% v 40%) and extraintestinal manifestations of Crohn's disease (0% v 40%). Histopathological features that seemed to reliably differentiate between intestinal tuberculosis and Crohn's disease included confluent granulomas, ⩾10 granulomas per biopsy site and caseous necrosis (in biopsy samples of 50%, 33% and 22% of patients with intestinal tuberculosis, respectively, v 0% of patients with Crohn's disease). Features that were observed more often in patients with intestinal tuberculosis than in those with Crohn's disease included granulomas exceeding 0.05 mm 2 (67% v 8%), ulcers lined by conglomerate epithelioid histiocytes (61% v 8%) and disproportionate submucosal inflammation (67% v 10%). Conclusion: Clinical features and selected histological parameters in colonoscopic biopsy specimens can help in differentiating between Crohn's disease and intestinal tuberculosis.